Microbial and heavy metal contamination in herbal medicine: a prospective study in the central region of Saudi Arabia - Sarah F. Alharbi; Ameerah I. Althbah; Amal H. Mohammed; Mishaal A. Alrasheed; Mukhtar Ismail; Khaled S. Allemailem; Abdullah M Alnuqaydan; Ahmed Mohammed Baabdullah; Azzam Alkhalifah (BMC, 2024)
Abstract Introduction Herbal medicine is a medical system based on the utilization of plants or plant extracts for therapy. The continual increase in global consumption and the trade of herbal medicine has raised safety concerns in many regions. These concerns are mainly linked to microbial contamination, which could spread infections with multi-resistant bacteria in the community, and heavy metal contamination that may lead to cancers or internal organs' toxicity. Methods This study was performed using an experimental design. A total of 47 samples, herbal medicine products sold in local stores in Qassim region, were used in the experiments. They were tested for bacterial contamination, alongside 32 samples for heavy metal analysis. Bacterial contamination was determined by the streak plate method and further processed to determine their antimicrobial susceptibility patterns using MicroScan WalkAway96 pulse; heavy metals were determined using a spectrometer instrument. Results A total of 58 microorganisms were isolated. All samples were found to be contaminated with at least one organism except three samples. The majority of the isolated bacterial species were gram negative bacteria, such as Klebsiella spp., Pseudomonas spp. and E. coli., which could be of fecal origin and may lead to pneumonia, skin, or internal infections. Furthermore, most of the gram-positive bacteria were found to be multi-drug resistant. Moreover, for heavy metals, all samples had levels exceeding the regulatory limits. Conclusion This study demonstrated the presence of bacteria and heavy metals in samples of herbal medicines. Using these contaminated products may spread resistant infections, metal toxicities, or even cancers in the community.